2006
DOI: 10.1080/09513590601010722
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of a combination of isoflavones, lignans andCimicifuga racemosaon climacteric-related symptoms in postmenopausal women: A double-blind, randomized, placebo-controlled trial

Abstract: The present study aimed to evaluate the short-term effects of a combination of isoflavones, lignans and Cimicifuga racemosa on acute climacteric-related symptoms in postmenopausal women in a double-blind, randomized, placebo-controlled trial performed at the menopause clinic of our department. Eighty healthy postmenopausal women were randomly assigned to two treatment groups - one receiving the combination (group A, n = 40), the other receiving calcium supplements (group B, n = 40) - for three cycles of 28 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
1
19
0
9
Order By: Relevance
“…Of the seven studies that reported KI data 17 20 , 23 25 , three reported a significant reduction of KI in the phytoestrogen group when compared with the placebo group 17 , 20 , 25 , while the other four 18 , 19 , 23 , 24 reported no difference between the groups. Meta-analysis of the seven studies indicated no significant treatment effect of phytoestrogen when compared to placebo (pooled mean difference = 6.4, p = 0.110, Figure 2a ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Of the seven studies that reported KI data 17 20 , 23 25 , three reported a significant reduction of KI in the phytoestrogen group when compared with the placebo group 17 , 20 , 25 , while the other four 18 , 19 , 23 , 24 reported no difference between the groups. Meta-analysis of the seven studies indicated no significant treatment effect of phytoestrogen when compared to placebo (pooled mean difference = 6.4, p = 0.110, Figure 2a ).…”
Section: Resultsmentioning
confidence: 97%
“…The number of participants in the studies ranged from 30 to 252, and the intervention periods ranged from 3 to 12 months. Seven studies reported the KI at baseline and after intervention 17 20 , 23 25 , while ten studies reported hot flush frequency at baseline and after intervention, or change from baseline 11 , 15 , 16 , 19 , 21 23 , 26 28 . As expected, there was no significant difference in baseline KI and hot flush frequency between treatment and placebo groups, since the participants were randomly allocated.…”
Section: Resultsmentioning
confidence: 99%
“…Isoflavones are absorbed and removed faster than lignans. Consistent with this, a large randomized study has shown that the combination of the different molecules is most efficacious for the control of postmenopausal symptoms during a 24 hour period [135]. …”
Section: Effects Of Phyto- and Xenoestrogens On Human Breast Tissuementioning
confidence: 67%
“…The mechanisms of action of this phytotherapeutic herb are still not totally understood, but there is growing interest in its usefulness in the treatment of vasomotor symptoms and hot flushes and in preventing the decrease in bone density associated with menopause [93, 94]. The use of black cohosh in clinical trials as an adjuvant to chemotherapy was observed to help patients improve their QOL through relief of vasomotor symptoms [95, 96]. Moreover, in vitro studies using MCF7 cells showed the high antitumor activity of C. racemosa extracts and their involvement in induction of apoptosis [97].…”
Section: Resultsmentioning
confidence: 99%